2021
DOI: 10.1101/2021.11.10.21266138
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 RNA is enriched by orders of magnitude in solid relative to liquid wastewater at publicly owned treatment works

Abstract: Wastewater-based epidemiology has gained attention throughout the world for detection of SARS-CoV-2 RNA in wastewater to supplement clinical testing. Methods have been developed using both the liquid and the solid fraction of wastewater, with some studies reporting higher concentrations in solids. To investigate this relationship further, we collaborated with six other laboratories to conduct a study across five publicly owned treatment works (POTWs) where both primary solids and raw wastewater influent sample… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3

Relationship

5
1

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…Previous studies showed that RNA from SARS-CoV-2 is naturally concentrated in primary settled solids at wastewater treatment plants. , Further, researchers have found a significant correlation between SARS-CoV-2 RNA isolated from primary settled solids samples and laboratory-confirmed COVID-19 cases; thus, settled solids might be an advantageous medium for wastewater-based epidemiology efforts. Laboratory-confirmed COVID-19 incidence may be considerably smaller than actual COVID-19 incidence owing to test-seeking behaviors which are influenced by testing availability and symptom presence and severity. , Some studies aim to infer actual COVID-19 incident cases from wastewater concentrations of SARS-CoV-2 RNA using models. Such models require the input of various parameters including fecal loads, viral shedding rates, flow to the wastewater treatment plant, the decay rate constant and partition coefficient of SARS-CoV-2 RNA, and the average residence time of wastewater prior to sample collection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies showed that RNA from SARS-CoV-2 is naturally concentrated in primary settled solids at wastewater treatment plants. , Further, researchers have found a significant correlation between SARS-CoV-2 RNA isolated from primary settled solids samples and laboratory-confirmed COVID-19 cases; thus, settled solids might be an advantageous medium for wastewater-based epidemiology efforts. Laboratory-confirmed COVID-19 incidence may be considerably smaller than actual COVID-19 incidence owing to test-seeking behaviors which are influenced by testing availability and symptom presence and severity. , Some studies aim to infer actual COVID-19 incident cases from wastewater concentrations of SARS-CoV-2 RNA using models. Such models require the input of various parameters including fecal loads, viral shedding rates, flow to the wastewater treatment plant, the decay rate constant and partition coefficient of SARS-CoV-2 RNA, and the average residence time of wastewater prior to sample collection.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that RNA from SARS-CoV-2 is naturally concentrated in primary settled solids at wastewater treatment plants. 1 , 2 Further, researchers have found a significant correlation between SARS-CoV-2 RNA isolated from primary settled solids samples and laboratory-confirmed COVID-19 cases; 3 7 thus, settled solids might be an advantageous medium for wastewater-based epidemiology efforts. Laboratory-confirmed COVID-19 incidence may be considerably smaller than actual COVID-19 incidence owing to test-seeking behaviors which are influenced by testing availability and symptom presence and severity.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, we developed and utilized assays for mutations characteristic of Alpha, Beta and Gamma (Beta/Gamma), Delta, Mu, Lambda, and Omicron and then measured these in wastewater solids from a publicly owned treatment work (POTW) located in the Bay Area of California, USA. We measured concentrations in wastewater settled solids, as concentrations of SARS-CoV-2 RNA are enriched several orders of magnitude in solids relative to those in liquid wastewater ( 20 , 21 ). We subsequently compared the measurements to data on occurrence of those variants in clinical specimens, aggregated at the state level.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that RNA from SARS-CoV-2 is naturally concentrated in primary settled solids at wastewater treatment plants. 1,2 Further, researchers have found a significant correlation between SARS-CoV-2 RNA isolated from primary settled solids samples and laboratoryconfirmed COVID-19 cases [3][4][5][6][7] thus, settled solids might be an advantageous medium for wastewater-based epidemiology efforts. Laboratory-confirmed COVID-19 incidence may be considerably smaller than actual COVID-19 incidence owing to test-seeking behaviors which are influenced by testing availability and symptom presence and severity.…”
Section: Introductionmentioning
confidence: 99%